Analysis of Lawsuit Against the Factual Action which Conducted by Military after Law Number 30 Year 2014 Concerning Government Administration - Wahyu Purnomo; Rr. Herini Siti Aisyah; Thoriq Mulahela; Xavier Nugraha (Unram Law Review, 2020)
The enactment of law Number 30 of 2014 on Government Administration has caused a paradigm shift under development of state administration decision (in short term known as KTUN). By virtue of article 87 of Law number 30 year 2014, KTUN was not only on the written form, but it can also be a factual act. This causes a change in the absolute competence of lawsuit on factual actions taken by the government from the district administrative court (PTUN). It is arises a question whether Article 87 of Law number 30 year 2014 also applies to claims for factual actions committed by the military. The formulation of problems in this research are 1) The position of a lawsuit against factual actions committed by the military before Law number 30 year 2014 and 2) the claim position against factual actions committed by the military after Law Number 30 Year 2014. This research is a doctrinal research by using a statute approach and conceptual approach. The result of the analysis found that the KTUN paradigm have change under Law number 30 year 2014, which does not affect the absolute competence of lawsuits for factual actions carried out by military, though a government were excluded as mentioned on Article 2 of Law Number 9 of 2004 on Amendments of Law Number 5 of 1986 concerning State Administrative Court. It was confirmed under Article 87 of Law 30/2014, which grammatically states that the only changes to the KTUN are those in Law 51/2009, Law 10/2004, and Law 5/1986. The application of lex specialist pictured under the act number 30 year 2014 which regulated the administrative decision by the government, however concerning the military only regulated under the act number 31 year 1997. Further, the absolute competence on handling the legal factual action by the military since the implementation of law number 30 year 2014 is still held in the district court.